A comparative study of InGaAs/InAsSb and InAs/InAsSb strained layer superlattices - Yin, H. X.; Wang, Zh.; Zhang, J.; Jiang, Zh.; Chang, Ch.; Deng, G. R.; Zhou, X. C.; Yang, J.; Lei, W.; Ji, R. B. (Frontiers in Materials, 2025)
Over the past decade, InAs/InAsSb superlattices and their photodetectors have been widely studied due to their potential applications in high-performance infrared detectors. However, InAs/InAsSb superlattice-based infrared (IR) detectors suffer from a serious limitation of deficient light absorption and the corresponding low quantum efficiency (QE). Recently, InGaAs/InAsSb type-II strained layer superlattices have been reported to have the capability to enhance the absorption of infrared light. In this study, we present a detailed comparative analysis on the optical properties, electrical properties, and detector performance of InGaAs/InAsSb and InAs/InAsSb strained layer superlattices. With the introduction of Ga into the InAs layers, the light absorption coefficient is observed to increase from 2,247 cm−1 for InAs/InAsSb superlattices to 3,442 cm−1 for InGaAs/InAsSb superlattices at the typical mid-wave infrared wavelength of 4.7 μm. However, this increase in light absorption coefficient does not boost the QE of the InGaAs/InAsSb superlattice detectors. Instead, quantum efficiency decreases from 45% for InAs/InAsSb superlattice detectors to 27% for InGaAs/InAsSb superlattice detectors at 150 K. This degradation in quantum efficiency for InGaAs/InAsSb superlattice detectors is found to be mainly caused by their poorer electrical properties, e.g., electron mobility and minority carrier lifetime. Fundamentally, the poorer electrical properties and lower quantum efficiency of InGaAs/InAsSb superlattice detectors are mainly due to the higher defect density within the materials, which is evidenced by the study of cross-sectional electron backscattered diffraction in these superlattices.